The implementation of halal logo and certification towards restaurant performance - Arsat, Alifaizi; Raja Azam, Raja Saidatul Hisan; Zulkifly, Muhammad Izzat; Bachok, Sabaianah; Baba, Noradhar (2010)
This study investigates the factors that can influence the implementation of Halal logo and certification. It also identifies the constraints on implementing the system by the respective restaurant and following with the impacts on implementing the system towards the restaurant performance. Sample populations of this study were among the manager or owner of the restaurant around Klang Valley which already implemented the system. Result from face-to-face interviews by using semi structured questions revealed that majority of the representatives believed that customers were the most important factor in implementing the Halal logo and certification. It also appears some constraints about the system namely the documentation, the implementations and resistance to change. The study also highlights several important points which should be beneficial to the government, restaurant industry, societies and other related agencies. Overall, some useful insights were obtained.